2020
DOI: 10.4103/jfmpc.jfmpc_971_19
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse and neglect in a rapidly developing country: Parents' perspectives

Abstract: Purpose: To identify parental awareness and knowledge regarding child abuse and neglect in the State of Qatar. Methods: A cross-sectional study using a questionnaire was conducted at Hamad Medical Corporation, the only tertiary pediatric hospital in the State of Qatar at the time of the study. Parents of children of all ages were offered a questionnaire that included demographic details, parental knowledge, and awareness of child abuse and neglect. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Barzeva et al (2019) showed that neglect and physical and sexual abuse are the most common types of abuse for these children. Hendaus et al (2020) showed that the most prominent thing that children with autism are exposed to is their contempt, underestimation, blame and deprivation of their legal rights, which makes them suffer from the inability to communicate with society. Cidav, Xie and Mandell (2018) indicated that there is a relationship between autistic child abuse and disability conditions, in addition to being less able to defend themselves compared to ordinary children when interacting with others.…”
Section: Discussionmentioning
confidence: 99%
“…Barzeva et al (2019) showed that neglect and physical and sexual abuse are the most common types of abuse for these children. Hendaus et al (2020) showed that the most prominent thing that children with autism are exposed to is their contempt, underestimation, blame and deprivation of their legal rights, which makes them suffer from the inability to communicate with society. Cidav, Xie and Mandell (2018) indicated that there is a relationship between autistic child abuse and disability conditions, in addition to being less able to defend themselves compared to ordinary children when interacting with others.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with the most recent study in Qatar determining parental views on child abuse and neglect where 63 per cent of parents were against hitting as a form of discipline and 62.8 per cent acknowledged that yelling is a form of child abuse. However, one quarter considered it acceptable to hit a child provided no injury resulted (Hendaus et al, 2020). That study differs from the present one in that it did not restrict itself to Qatari nationals but included residents in Qatar without giving their countries of origin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study found that mothers in nine low-and middle-income countries who believed VDMs are necessary to rear their child were eight times more likely to report that they or another caregiver had used physical and psychological violence on their child (Lansford et al, 2014). As mentioned above, the study in Qatar by Hendaus et al (2020) also points to a disconnect between belief and action. In addition, in Saudi Arabia, a neighbouring country to Qatar that shares multiple similarities in terms of historical, cultural, economic, as well as religious context, has a similar pattern to that observed in our study as parents who believed that it was acceptable to hit their child as form of discipline, or that hitting their child was not a form of child abuse, were significantly more likely to use VDMs (Al Dosari et al, 2017).…”
Section: Mother's Beliefs In Comparison To Their Actionsmentioning
confidence: 91%
“…The questionnaire was developed considering previous studies carried out in the Middle East. [ 18 , 19 , 21 , 22 ] Participants’ knowledge was classified into three response categories (agree, disagree, or don’t know), and their perception was recorded using a 5-point Likert scale (1 = strongly disagree; 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%